2020
DOI: 10.3390/su122410295
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Power Prediction Using Artificial Neural Networks and Numerical Weather Data

Abstract: The monitoring of power generation installations is key for modelling and predicting their future behaviour. Many renewable energy generation systems, such as photovoltaic panels and wind turbines, strongly depend on weather conditions. However, in situ measurements of relevant weather variables are not always taken into account when designing monitoring systems, and only power output is available. This paper aims to combine data from a Numerical Weather Prediction model with machine learning tools in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Photovoltaic installations are very popular because they are available to most people, and their installation does not require as much capital as in the case of installations using other renewable energy sources which is confirmed by many authors in their works [1][2][3][4][5]. In addition, along with the development of technology, they are becoming cheaper and more effective way to obtain electricity [6][7][8]. Currently, little attention is paid to the problem of recycling waste generated as a result of the development of the photovoltaic industry, but in the coming years it may turn out to be a big mistake.…”
Section: Introductionmentioning
confidence: 93%
“…Photovoltaic installations are very popular because they are available to most people, and their installation does not require as much capital as in the case of installations using other renewable energy sources which is confirmed by many authors in their works [1][2][3][4][5]. In addition, along with the development of technology, they are becoming cheaper and more effective way to obtain electricity [6][7][8]. Currently, little attention is paid to the problem of recycling waste generated as a result of the development of the photovoltaic industry, but in the coming years it may turn out to be a big mistake.…”
Section: Introductionmentioning
confidence: 93%
“…In this paper, it was shown that adding time series inputs, in the form of common weather variables, does not improve the current ANN model. Gomes et al [18] forecasted the solar resource in a 4-h time horizon, using meteorological variables as inputs to the ANN.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, domestic and foreign scholars have done a lot of research on the short-term prediction of optical volt power in the direct method to solve the problems of photovoltaic grid connection to maintain the stability of the power system. Researchers have successively proposed support vector machine (SVM) (Mayer and Gróf, 2021), Markov chain (Hu and Zhang, 2018), limit learning machine (Wang, 2018), artificial neural network (ANN) (López Gómez et al, 2020), time series prediction and other methods (Zhu et al, 2019;Singh et al, 2021). Traditional ANN achieves power prediction by establishing a mapping between input data and output data, and the lack of consideration of time correlation in the data series makes it impossible for neural network models to capture the relationship between data and time, which limits its application in time series forecasting methods.…”
Section: Introductionmentioning
confidence: 99%